Polyethylene glycol‐fused allografts produce rapid behavioral recovery after ablation of sciatic nerve segments. Issue 4 (25th November 2014) - Riley, D.C.; Bittner, G.D.; Mikesh, M.; Cardwell, N.L.; Pollins, A.C.; Ghergherehchi, C.L.; Bhupanapadu Sunkesula, S.R.; Ha, T.N.; Hall, B.T.D.; Poon, A.D.; Pyarali, M.; Boyer, R.B.; et al.
Abstract : Restoration of neuronal functions by outgrowths regenerating at ∼1 mm/day from the proximal stumps of severed peripheral nerves takes many weeks or months, if it occurs at all, especially after ablation of nerve segments. Distal segments of severed axons typically degenerate in 1–3 days. This study shows that Wallerian degeneration can be prevented or retarded, and lost behavioral function can be restored, following ablation of 0.5–1‐cm segments of rat sciatic nerves in host animals. This is achieved by using 0.8–1.1‐cm microsutured donor allografts treated with bioengineereds olutions varying in ionic and polyethylene glycol (PEG) concentrations (modified PEG‐fusion procedure), being careful not to stretch any portion of donor or host sciatic nerves. The data show that PEG fusion permanently restores axonal continuity within minutes, as initially assessed by action potential conduction and intracellular diffusion of dye. Behavioral functions mediated by the sciatic nerve are largely restored within 2–4 weeks, as measured by the sciatic functional index. Increased restoration of sciatic behavioral functions after ablating 0.5–1‐cm segments is associated with greater numbers of viable myelinated axons within and distal to PEG‐fused allografts. Many such viable myelinated axons are almost certainly spared from Wallerian degeneration by PEG fusion. PEG fusion of donor allografts may produce a paradigm shift in the treatment of peripheral nerve injuries. © 2014 Wiley Periodicals, Inc.